2021
DOI: 10.1093/pcp/pcab027
|View full text |Cite
|
Sign up to set email alerts
|

Phototropin Interactions with SUMO Proteins

Abstract: The disruption of the sumoylation pathway affects processes controlled by the two phototropins of Arabidopsis thaliana, phot1 and phot2. Phototropins, plant UVA/blue light photoreceptors, regulate growth responses and fast movements aimed at optimizing photosynthesis, such as phototropism, chloroplast relocations and stomatal opening. Sumoylation is a posttranslational modification, consisting in the addition of a SUMO (SMALL UBIQUITIN-RELATED MODIFIER) protein to a lysine residue in the target protein. Beside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 64 publications
(107 reference statements)
0
1
0
Order By: Relevance
“…It is also tempting to speculate that SUMOylation alters the formation of phytochrome heterodimers, providing an extra fine‐tuning mechanism to phytochrome light sensing. Furthermore, a recent report demonstrated that the blue light photoreceptor phototropin 2 is SUMOylated, but its physiological significance is not known (Łabuz et al ., 2021), indicating that SUMO modification of plant photoreceptors is not exclusive to phyB but is a general fine‐tuning mechanism of light signaling (Table 2).…”
Section: Discussion and Future Perspectivesmentioning
confidence: 99%
“…It is also tempting to speculate that SUMOylation alters the formation of phytochrome heterodimers, providing an extra fine‐tuning mechanism to phytochrome light sensing. Furthermore, a recent report demonstrated that the blue light photoreceptor phototropin 2 is SUMOylated, but its physiological significance is not known (Łabuz et al ., 2021), indicating that SUMO modification of plant photoreceptors is not exclusive to phyB but is a general fine‐tuning mechanism of light signaling (Table 2).…”
Section: Discussion and Future Perspectivesmentioning
confidence: 99%